(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2020)
This piece explores and analyzes Diane Arbus’ infamous Untitledseries, a collection of photographs documenting institutions for individuals with disabilities in the late 1960s. While immense controversy surrounds her work, this paper argues that although there are shortcomings in these images and her oeuvre as whole, the Untitled series is ultimately on the right side of history. For additional context, listen to the author’s reflection on the piece below.